2013
DOI: 10.1007/978-3-319-03753-0_1
|View full text |Cite
|
Sign up to set email alerts
|

A Populated Iterated Greedy Algorithm with Inver-Over Operator for Traveling Salesman Problem

Abstract: Abstract. In this study, we propose a populated iterated greedy algorithm with an Inver-Over operator to solve the traveling salesman problem. The iterated greedy (IG) algorithm is mainly based on the central procedures of destruction and construction. The basic idea behind it is to remove some solution components from a current solution and reconstruct them in the partial solution to obtain the complete solution again. In this paper, we apply this idea in a populated manner (IGP) to the traveling salesman pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The combination of operators in GA-TSP4 reflects a better computational performance than operators recently reported in the literature. For this comparison, the following operators were considered: GSTM [ 63 ], MIO [ 65 ], MA_IO [ 66 ], and IGP_IO [ 67 ]. The comparisons are shown in Table 12 .…”
Section: Resultsmentioning
confidence: 99%
“…The combination of operators in GA-TSP4 reflects a better computational performance than operators recently reported in the literature. For this comparison, the following operators were considered: GSTM [ 63 ], MIO [ 65 ], MA_IO [ 66 ], and IGP_IO [ 67 ]. The comparisons are shown in Table 12 .…”
Section: Resultsmentioning
confidence: 99%
“…For the small‐scale instances, 500 different runs with the selected parameters (in Table ) were performed for each of the benchmark instances. The solutions for the same instances of CEO and three other algorithms, honey‐bee mating optimization (HBMO) (Marinakis, Marinaki, and Dounias ), greedy subtour mutation (GSTM) (Albayrak and Allahverdi, ), and populated iterated greedy algorithm with inver‐over operator (IGP_IO) (Tasgetiren et al ), are shown in Table . From Table (the optimal solution has been highlighted), the following could be observed: CEO and HBMO can always find the optimal solution in a short time for all the instances, while GSTM and IGP_IO cannot. The HBMO is a competitive algorithm with all the best solution equaling optimum; however, the running time of CEO is almost half of that of HBMO.…”
Section: Simulations and Comparisonsmentioning
confidence: 99%
“…The IG algorithm is initially proposed by Feo and Resende [26]. It has been widely used to optimise numerous optimisation problems across various fields, such as combinatorial optimisation problems [27][28][29][30], feature selection, and data mining [31]. The IG algorithm is also used in manufacturing systems to solve flowshop scheduling problems, including flowshop [32], hybrid flowshop [33], flexible job shop (FJS) [34], and distributed flowshop [35].…”
mentioning
confidence: 99%